PLANNING AND MANUFACTURING OF TRANSMISSION OF CORN COB COUNTING EQUIPMENT USING 1 HP ELECTRIC MOTOR WITH A CAPACITY OF 2 KG PER 5 MINUTES - Nasution, Ahmad Yunus; Effendi, Riki; Najamudin, Muhammad (Universitas Muhammadiyah Jakarta, 2021)
Corn cobs are a cultural problem in the NTB region because they are very influential at post-harvest harvesting. Poor handling of post-harvest corn cobs is a very serious problem in the area. Where corn cobs are only used by the community in general, making corn cobs as a mosquito repellent, by burning corn cobs. Corn cobs are corn residues resulting from shelling seeds which contain potential compounds that can be biologically transformed into other compounds, namely lignin, cellulose and hemicellulose. For example, making corn cobs chopper as a tool in handling post-harvest results. The purpose of this plan is to produce an efficient corn cob chopping machine so that it is useful for the community in NTB. The results of observations from the previous tool and processing data will be used to make the design size of the corncob chopper according to the real conditions of the previous tool. The results of the calculation of the transmission system of the corn cob chopper showed that the rotation of the electric motor was 1 HP = 1400 rpm, the shaft diameter was 20 mm, the seat belt used type A with a length of 828.4 mm. The materials used in this corncob chopping knife are as follows: knife = stainless steel material, bearing = cast iron, vant belt = rubber, pulley = aluminum, shaft = S35C-D. From the results of testing the corn cob chopper, 2 kg was obtained in 5 minutes.